Pengembangan Bahan Ajar Berbasis Kearifan Lokal untuk Meningkatkan Keterampilan Berpikir Tingkat Tinggi (HOTS) pada Guru SD YPK Ifar Babrongko, Sentani - Kadir, Akhmad; Sumawan (Universitas Cenderawasih, 2024)
This community service activity aims to develop local wisdom-based teaching materials to improve higher order thinking skills (HOTS) in elementary school teachers at YPK Ifar Babrongko, Yoboi Village, Sentani, Jayapura. The implementation of the activity includes training and mentoring teachers in compiling teaching materials that are relevant to local potential, such as environmental management and local culture. The results showed high enthusiasm from participants and awareness of the importance of integrating local wisdom in learning. This article discusses strategies, results, and potential for further development.